"How does one lay to rest the ghost of Faulkner?": William Faulkner as Coetzeean "counter voice". Issue 4 (2nd October 2019) - Foxton, Hannah
ABSTRACT: This article explores J. M. Coetzee's evolving literary relationship to William Faulkner by examining Coetzee's published and unpublished works, including materials found in the Harry Ransom Center and the Amazwi Museum of South African Literature. Throughout his career, Coetzee regarded Faulkner as a writer whose primary concern was to tell and retell the epic of a particular historical moment. The way that Coetzee writes and thinks about Faulkner can be seen as a touchstone of how he thought about the impact that his Afrikaner identity would have on his literary output. Coetzee moves from an "obscure combat" with Faulkner in Dusklands and In the Heart of the Country, to a less fraught relationship of diminishing significance in his later work. In Waiting for the Barbarians, Coetzee continued to "converse" with Faulkner intertextually, but treats him as a "Counter voice" to shape his work, ultimately deviating from Faulkner's style and ideas.